Limit theorem for coiuntable systems of stochastic differential equations - Pilipenko, A. Yu.; Tantsiura, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We consider infinite systems of stochastic differential equations used to describe the motion of interacting particles inrandom media. It is assumed that mass of each particle tends to zero and the density of particles infinitely increases in aproper way. It is proved that the sequence of the corresponding measure-valued processes converges in distribution. Wealso prove existence and uniqueness of a strong solution for the limit equation.